Fatores de risco para mastite bovina e avaliação fenotípica de resistência antimicrobiana - Almeida, Thamara Venâncio de (2020)
Bovine mastitis is the most common disease that causes the most economic losses in dairy herds around the world. The objective of this study was to evaluate the risk factors for subclinical mastitis in dairy herds in the State of Goiás, to identify the gram-positive microorganisms that cause mastitis, as well as their antimicrobial resistance. Milk samples were collected from 1,034 lactating cows from 27 dairy farms located in the State of Goiás and analyzes of somatic cell count (SCC), bacterial examination and antimicrobial sensitivity test were performed. A checklist was applied to each participating property to obtain data on the animals, the properties and the hygienic and sanitary management of the herds. Risk factors for mastitis were assessed using a mixed generalized linear model. Of the 27 properties, 11 (40.74%) had SCC of the tank above 500,000 cells/mL, therefore above the maximum limit established by Brazilian legislation. The prevalence of subclinical mastitis in herds (SCC> 200,000 cells / mL) was 54.93%. The main risk factors associated with the occurrence of subclinical mastitis in dairy cows were old age, pendulous udder and advanced lactation stage. 216 microorganisms were identified, gram-positive cocci. Staphylococcus spp. (53.10%), particularly S. aureus (30.09%), stood out as one of the most common agents involved in the etiology of bovine subclinical mastitis, followed by Streptococcus spp. (22.12%) and Enterococcus sp. (16.81%). The highest rates of antimicrobial resistance were Staphylococcus aureus to penicillin (76%) and ampicillin (74%), Streptococcus spp. to neomycin (65.08%), gentamicin (46.03) and tetracycline (43.66%) and Enterococcus spp. tetracycline (52.38%). Isolates of Streptococcus spp. multiresistant (18.06%).